2013
DOI: 10.1128/ec.00249-12
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the Mating-Type (MAT) Locus That Controls Sexual Reproduction of Blastomyces dermatitidis

Abstract: c Blastomyces dermatitidis is a dimorphic fungal pathogen that primarily causes blastomycosis in the midwestern and northern United States and Canada. While the genes controlling sexual development have been known for a long time, the genes controlling sexual reproduction of B. dermatitidis (teleomorph, Ajellomyces dermatitidis) are unknown. We identified the mating-type (MAT) locus in the B. dermatitidis genome by comparative genomic approaches. The B. dermatitidis MAT locus resembles those of other dimorphic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(38 citation statements)
references
References 47 publications
(69 reference statements)
0
37
0
1
Order By: Relevance
“…A MAT1-2-4 gene has also been reported for Coccidioides immitis and C. posadasii (51, 52), but this shares little sequence conservation with the MAT1-2-4 proteins from the aspergilli and is absent from the MAT loci of many other heterothallic eurotiomycete species, such as those recently described for Blastomyces dermatitidis (53). …”
Section: Resultsmentioning
confidence: 93%
“…A MAT1-2-4 gene has also been reported for Coccidioides immitis and C. posadasii (51, 52), but this shares little sequence conservation with the MAT1-2-4 proteins from the aspergilli and is absent from the MAT loci of many other heterothallic eurotiomycete species, such as those recently described for Blastomyces dermatitidis (53). …”
Section: Resultsmentioning
confidence: 93%
“…Recently, a MAT locus was identified in the ascomycete Blastomyces dermatitidis 151 . This dimorphic fungal pathogen is the leading cause of blastomycosis, causing severe respiratory and disseminated disease in immunocompetent humans.…”
Section: Sex In Other Human Fungal Pathogensmentioning
confidence: 99%
“…Distribution of mating types and population genetics studies suggest that B. dermatitidis might reproduce sexually, but the mating-type locus had not been described 152,153 . The identification of the B. dermatitidis MAT revealed that, unlike the MAT loci of other dimorphic fungi, it contains transposable elements (TEs) that make it unusually large and may increase sequence diversity between the two MAT idiomorphs while decreasing recombination within this region 151 . It remains unclear, however, if this fungus undergoes sexual reproduction in nature and, if so, whether the resulting sexual spores are infectious.…”
Section: Sex In Other Human Fungal Pathogensmentioning
confidence: 99%
“…Very little work has been done exploring genetic recombination in B. dermatitidis . Although B. dermatitidis can reproduce sexually, the mating-type locus was only recently identified [25], and it is unknown how frequently sexual reproduction occurs in nature. The rate of recombination between and among the 2 major genetic groups of B. dermatitidis could significantly impact the population genetic structure of this pathogen.…”
Section: Discussionmentioning
confidence: 99%